Lifetime Trauma History and Cognitive Functioning in Major Depression and Their Role for Cognitive-Behavioral Therapy Outcome - Schindler, Lena; Stalder, Tobias; Kirschbaum, Clemens; Plessow, Franziska; Schoenfeld, Sabine; Hoyer, Jürgen; Trautmann, Sebastian; Weidner, Kerstin; Steudte-Schmiedgen, Susann (Clinical Psychology in Europe, 2021)
Background: While cognitive-behavioral therapy (CBT) is the gold-standard psychological treatment for major depression (MD), non-response and lacking stability of treatment gains are persistent issues. Potential factors influencing treatment outcome might be lifetime trauma history and possibly associated primarily prefrontal-cortex- and hippocampus-dependent cognitive alterations. Method: We investigated MD and healthy control participants with (MD+T+, n = 37; MD-T+, n = 39) and without lifetime trauma history (MD+T-, n = 26; MD-T-, n = 45) regarding working memory, interference susceptibility, conflict adaptation, and autobiographical memory specificity. Further, MD+T+ (n = 21) and MD+T- groups (n = 16) were re-examined after 25 CBT sessions, with MD-T- individuals (n = 34) invited in parallel in order to explore the stability of cognitive. This is an open access article distributed under the terms of the Creative Commons Attribution 4.0 International License, CC BY 4.0, which permits unrestricted use, distribution, and reproduction, provided the original work is properly cited. alterations and the predictive value of lifetime trauma history, cognitive functioning, and their interaction for treatment outcome. Results: On a cross-sectional level, MD+T+ showed the highest conflict adaptation, but MD+T- the lowest autobiographical memory specificity, while no group differences emerged for working memory and interference susceptibility. Clinical improvement did not differ between groups and cognitive functioning remained stable over CBT. Further, only a singular predictive association of forward digit span, but no other facets of baseline cognitive functioning, lifetime trauma history, or their interaction with treatment outcome emerged. Discussion: These results indicate differential roles of lifetime trauma history and psychopathology for cognitive functioning in MD, and add to the emerging literature on considering cognitive, next to clinical remission as a relevant treatment outcome.
Created from Fastlane, Scopus look-up
Keywords: Autobiographical memory; Cognitive-behavioral therapy; Conflict adaptation; Interference susceptibility; Lifetime trauma history; Major depression; Working memory